In Vivo Measurement of Root Canal Wall Temperature at Different Stages Prior to Fiber Post Cementation - Caiado, Ana Carolina Rocha Lima; Azevedo, Cristiana Godoy Sartori; Giannini, Marcelo; De Goes, Mario Fernando; Rueggeberg, Frederick Allen (European Journal of Dentistry, 2019)
Objective This study measured the in vivo temperature of prepared root canal walls during various stages of treatment prior to endodontic postcementation.Materials and Methods One tooth each from five patients requiring endodontic treatment received conventional gutta-percha obturation. The coronal 4 mm of gutta-percha was removed by drilling and the canal wall temperature was measured. A sterile, saline rinse was applied, and another temperature value was recorded. Paper points were placed, and the wall temperature was recorded. A standardized period of 1.5 minute passed, simulating time needed to mix and place the resin cement and post (no resin was placed), after which the final wall temperature was obtained. The tooth was temporized and scheduled for prosthetic reconstruction. A one-way repeated measure analysis of variance (with Tukey's post hoc test) was performed among mean temperature values for each treatment stage (preset α 0.05).Results Significant temperature differences were found among the treatment stages. Canal space drilling yielded the highest temperature (35.5 ± 0.8°C), while the lowest was obtained after saline rinsing (34.0 ± 0.9°C). The temperature of prepared root canal wall prior to postplacement (34.9 ± 1.2°C) and following paper point drying (34.8 ± 1.1°C) presented intermediate results, with no statistical difference between them.Conclusions This study suggested that root canal wall temperature varied during various stages of preparation prior to endodontic post.
Keywords: postcementation; postspace preparation; resin cement; root canal wall temperature